«Du må bare skrive ut, ønske lykke til, og stole på at det går bra!» En kvalitativ undersøkelse av sykepleieres muligheter og begrensninger for skjønnsutøvelse når pasienter skal utskrives fra sykehus til kommunale helse- og omsorgstjenester. - Handeland, Jorunn Aas; Tveit, Bodil (Nordisk Tidsskrift for Helseforskning, 2015)
“You can only discharge them, wish them luck, and hope for the best!” The aim was to investigate nurse’s experiences of the possibilities to act according to their professional discretion in the process where patients are transferred from hospital to primary health services. Six in-depth interviews and one focus group interview with hospital nurses were conducted. The theoretical framework was based on Dworkin’s concepts of discretion and Martinsen’s description of prerequisites for discretion. Nurses collected and assessed complex information about the patients to be able to define the necessary level of care after discharge. Prerequisites for a robust assessment were adequate time, and the relationship to patients. Focus on effectivity, medical treatment, and limited possibilities to hand over their assessments to the municipal health services, created challenges. Nurses were negotiating between professional ideals and requirements from regulations. This created a potential conflict within the nurses between a professional role and a performer role, which in turn can lead to problematic consequences, both for nurses and for patients.